Quality of life issues related to organ sparing - Tannock, Ian (Radiology and oncology (Ljubljana), 2000)
The aim of organ sparing procedures is to maintain survival with a level of quality of life (QL) that is as high as possible. Methods are now available for evaluating QL in patients treated by quite different strategies and shouldbe included as major endpoints, together with survival, in future clinical trials that investigate organ-sparing strategies. These methods will be useful in decision aiding for strategies leading to similar survival, and in framing choices between improved quality and improved quantity of survival.
Keywords: Cystectomy; kvaliteta življenja; Laryngectomy; Methods; Neoplasms; onkologija; Quality of life; Surgery; Survival analysis; zdravljenje